Colposcopy and directed biopsy in the diagnosis of cervical cancer - Lazo Martínez, Armando (2015)
This work presented was intended to demonstrate personal observations on 400 patients who attended the outpatient clinic No. 6 the incidence of cervical cancer with the help of three methods simultaneously are: a) Colposcopy; b) Cytology; c) directed biopsy. We also try to describe the modus operandi, the frequency of typical and atypical colposcopic images, the index of malignancy of atypical images.